2017
DOI: 10.4236/ojemd.2017.74011
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Safety and Efficacy of Glaritus<sup>®</sup> versus Lantus<sup>®</sup> in Combination with Insulin Lispro among Adults with Type 1 Diabetes Mellitus-Phase IV Study

Abstract: Objective: The present study assessed safety and efficacy of Glaritus® among adults with Type 1 Diabetes Mellitus (T1DM). Methodology: This prospective, randomized, multicenter, comparative, non-inferiority, open-label, parallel group, phase IV study was conducted in 14 study centers in India. Subjects were randomly allocated to receive either Glaritus® or Lantus® for 12 weeks. Each week, the dose of insulin was titrated to maintain target fasting blood glucose (FBG) level range of 80 -120 mg/dL. Results: A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…In phase IV study in 161 type 1 diabetics, Glaritus® was found comparable to Lantus® in terms of glycemic control (mean reduction in HbA1c from baseline 0.69% ± 1.81% vs. 0.53% ± 1.94%, respectively; P = 0.454), incidence of hypoglycaemia (27.2% vs. 28.6%, P = 0.8432) and immunogenicity (mean reduction in AIA from baseline 0.25 ± 0.97 vs. 0.02 ± 0.68, respectively; P = 0.306) over 12 weeks of treatment [31]. Open Journal of Endocrine and Metabolic Diseases…”
Section: Background and Rationalementioning
confidence: 98%
“…In phase IV study in 161 type 1 diabetics, Glaritus® was found comparable to Lantus® in terms of glycemic control (mean reduction in HbA1c from baseline 0.69% ± 1.81% vs. 0.53% ± 1.94%, respectively; P = 0.454), incidence of hypoglycaemia (27.2% vs. 28.6%, P = 0.8432) and immunogenicity (mean reduction in AIA from baseline 0.25 ± 0.97 vs. 0.02 ± 0.68, respectively; P = 0.306) over 12 weeks of treatment [31]. Open Journal of Endocrine and Metabolic Diseases…”
Section: Background and Rationalementioning
confidence: 98%
“…Glaritus® and Lantus are bioequivalent, according to research involving healthy volunteers. 26 In a 12-week trial of adult patients with T1DM, Glaritus®, a biosimilar insulin glargine, was found to have glycemic control that was on par with Lantus®. 27,28…”
Section: Glaritus®mentioning
confidence: 99%